Development of the Problem-Based Learning Activities Model for Enhancing Social Skills of Preservice Teachers - soparat, sasithorn (Journal of Graduate Research, 2026)
The objectives of this research were to: 1) develop and evaluate a problem-based learning activity model for enhancing the social skills of preservice teachers, and 2) examine the effects of the developed model. The population consisted of 986 preservice teachers enrolled in the Professional Practicum Course in the 2024 academic year. The sample consisted of two clusters of preservice teachers selected through cluster random sampling: 16 second-year students and 21 third-year students. The study employed a one-group posttest-only experimental design. The research instruments consisted of: 1) a problem-based learning activity model for enhancing the social skills of preservice teachers, 2) a social skills test, and 3) a questionnaire on mentor teachers’ and supervising instructors’ perceptions of preservice teachers’ social skill behaviors. Data were analyzed using mean, standard deviation, one-sample t-test, independent-samples t-test, and content analysis. The findings revealed that: 1) the developed problem-based learning activity model for enhancing the social skills of preservice teachers consisted of four major components, including a six-step PBL process and five social-skill enhancement activities, and the quality of the model was evaluated at a very high level in terms of feasibility ( = 4.52, S.D. = 0.18) and usefulness ( = 4.52, S.D. = 0.11), and at a high level in terms of appropriateness ( = 4.48, S.D. = 0.18) and accuracy ( = 4.36, S.D. = 0.17); 2) the students’ posttest social skill scores were significantly higher than the 80 percent criterion at the .01 level of statistical significance; 4) the third-year students obtained significantly higher social skill scores than the second-year students at the .05 level of statistical significance; and 5) according to the perceptions of mentor teachers and supervising instructors, the overall social skills of the preservice teachers were rated at a high level ( = 4.50, S.D. = 0.16).